Pengaruh Persepsi Kemudahan Berbelanja, Reputasi Website, Dan Kualitas Website Terhadap Minat Beli Online: Kepercayaan Sebagai Variabel Mediasi - Wiendy Deborah; Keni (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aims to determine the main factors that can influence the purchase intention from consumers. Based on previous research, three independent variables were obtained: perceptions of ease to use, website reputation, website quality and one intervening variable; trust that can attract purchase intention. This is a descriptive research by using questionnaire which distributed to 164 respondents in Jakarta area. Data was collected by using non probability sampling method. Regression analysis were used for data analysis by using SPSS. From this study, it was found that the influence of each variables can directly and indirectly influence purchase intention significantly.